PREDICTIONS OF 3-DIMENSIONAL STEADY AND UNSTEADY INVISCID TRANSONIC STATOR ROTOR INTERACTION WITH INLET RADIAL TEMPERATURE NONUNIFORMITY - Saxer, A; Giles, M (1994)
Numerical predictions of three-dimensional inviscid, transonic steady and periodic unsteady flow within an axial turbine stage are analyzed in this paper. As a first case, the unsteady effects of the stator trailing edge shock wave impinging on the downstream rotor are presented. Local static pressure fluctuations up to 60 percent of the inlet stagnation pressure are observed on the rotor suction side. The second case is an analysis of the rotor-relative radial secondary flow produced by a spanwise parabolic nonuniform temperature profile at the stator inlet. The generation of local hot spots is observed on both sides of the rotor blade behind the passing shock waves. The magnitude of the unsteady stagnation temperature fluctuations is larger than the time-averaged rotor inlet disturbance. In both cases, steady, unsteady, and time-averaged solutions are presented and compared. From these studies, it is concluded that the steady-state solution in static pressure matches well with the time-averaged periodic unsteady flow field. However, for the stagnation temperature distribution only the trend of the time-averaged solution is modeled in the steady-state solution.